Reforma Paktu Stabilizacji i Wzrostu. W kierunku wzrostu stabilności gospodarczej w Unii Europejskiej? - Baran, Bernadeta (Reform of the Stability and Growth Pact. Toward In crease of the Economical Stability in the European Union?, 2007)
In the first five years of the EMU, the economic governance framework did a good job in contributing to the establishment of macroeconomic stability. However, further improvements were essential to ensure the sustainability of public finances, to increase contribution to the growth and reflect the growing economic diversity in the Union. Many economists agree, that reinforcing the link between the EU rules and economic reality, by increasing the standing and effectiveness of this framework, would go in the right direction. The most important thing is, that the window of opportunity to make these improvements should not be wasted.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (15); 2007; nr 1166, s. 106-120